Análisis de la gestión de inventarios de la empresa M y L Medical E.I.R.L., periodo 2017 - 2021 - Ruiz Garcia, Cinthya (2022)
The company M Y L MEDICAL E.I.R.L. from the city of Iquitos, markets the sale of pharmaceutical and medical products, and maintains a stock of 950 items. Inventory management is always a concern for companies as they need to have a high turnover of their merchandise in order to avoid a high financial cost and higher storage expenses; Therefore, the objective of this thesis was to analyze the inventory management of the company M Y L MEDICAL E.I.R.L., in the period 2017 - 2021, for this, the present Descriptive and Non-Experimental design research was carried out, analyzing the behavior of the purchases and sales of merchandise, the initial inventory, the final inventory, the turnover of inventories and the cost of sales. After the analysis and discussion of the results, it was found that the value of merchandise sales was higher than the value of purchases, because the sales value contains the profit margin, and also due to the use of inventory balances. On the other hand, the inventory turnover during the 2017-2021 period fluctuated in the 2017-2019 period, reporting a turnover of 6.39 inventory turns in 2018. The lowest turnovers were reported in 2020 and 2021 with 0.40 and 0.64 inventory turns, respectively, indicating that much of the merchandise purchased in a period is being sold, which is positive for the company. When the cost of sales was analyzed, in 2020, it decreased considerably by -75.09% compared to the previous year, to later recover in 2021, increasing by 167.38%, which shows a variable behavior year by year during the period 2017 - 2021. On the other hand, the company M Y L MEDICAL E.I.R.L. incurred excessive inventory at the end of 2016, as a result of the start of its activities in October of that year, added to the closure of activities in March 2020 due to the Covid19 pandemic.